Parallel evolutionary optimization of structures - Thierauf, Georg; Cai, Jianbo (Computer Assisted Methods in Engineering and Science; Vol 7 No 4 (2000), 2023)
By introducing a variable coding technique, a parallel optimization method based on a combination of GAs and ESs is presented. The advantages of both GAs and ESs, like coding of genetic information and adaptation of optimization parameters, are enhanced by this new method.